Why Event Studies Do Not Detect Anti-Competitive Mergers - Sven-Olof Fridolfsson; Johan Stennek (The Research Institute of Industrial Economics (IUI), 2000)
Anticompetitive mergers increase competitors' profits, since they reduce competition. Using a model of endogenous mergers, we show that such mergers nevertheless may reduce the competitors' share-prices. Thus, event-studies can not detect anti-competitive mergers.
Keywords: G14; G34; L12; L41; 330; Mergers & Acquisitions; Event Studies; Antitrust; Coalition Formation; Fusion; Wohlfahrtsanalyse; Börsenkurs; Theorie